Properties of Natural Intermediate Band in Cu2CdGeS4 for Intermediate Band Solar Cells: A First-Principle Insight - Rasukkannu, Murugesan; Velauthapillai, Dhayalan; Vajeeston, Ponniah (University of Jaffna, 2019)
The development of intermediate band solar cells is an intermediate band in the band gap of the semiconductor, but it is generally produced artificially, which executes practical challenges on the synthesis side. Here, we found the natural intermediate band in the main band gap of Cu2CdGeS4 by first-principle calculations. Cu2CdGeS4 is I2-II-IV-VI4 group quaternary chalcogenide semiconductor, which had been proposed as promising light-absorber layer efficiency of Cu-based chalcogenide. For the first time, we found the isolated conduction band of Cu2CdGeS4 in the zincblende or wurtzite structure, which can be regarded as a natural intermediate band (partially filled) by employing a hybrid functional model. This evidence for the first time that absorption coefficient of both valance band to intermediate band and intermediate band to conduction band transition involving intermediate band are of significant by employing BSE method and corresponding to electronic transitions. The results imply that Cu2CdGeS4 being two-photon absorption in the visible light range. Additionally, the hole and electron effective masses of Cu2CdGeS4 are systematically studied using first-principle calculations. We show that Cu2CdGeS4 could make possible intermediate band solar cells of improved efficiency